Initial Interactions of Subgenus D Adenoviruses with A549 Cellular Receptors: Sialic Acid versus α(v) Integrins - Arnberg, Niklas (American Society for Microbiology, 2000)
Selected members of the adenovirus family have been shown to interact with the coxsackie adenovirus receptor, α(v) integrins, and sialic acid on target cells. Initial interactions of subgenus D adenoviruses with target cells have until now been poorly characterized. Here, we demonstrate that adenovirus type 8 (Ad8), Ad19a, and Ad37 use sialic acid as a functional cellular receptor, whereas the Ad9 and Ad19 prototypes do not.